Plan de promoción para el almacén promociones “Tulcán” del cantón Quevedo, año 2012 - Hernández Morán, María Graciela (2012)
The company Promotions Tulcán, seller of all kinds of fabrics, this in very competed business, exist very economic fabrics that come from the China across Panama, Peru, this does that for the factor I boast it is very difficult to compete. The strategy of differentiation that must have his products as for the materials, designs is fundamental for the survival, his specialized training directed specially the part of the area of Marketing that is the critical process that defines the aspect on the market is important in this fashionable business. Reason for which one has proceeded to apply a plan of promotion and marketing, where the Company is favored, allowing us to do substantial improvements which results will be seen specially the present year. The Company considers to grow one of 30 % in his sales approximately, on the basis of a strategic plan of marketing and promotion, this undoubtedly goes there is necessary to improve our sales, since one expects to have a tidy growth, prioritizing specially his liquidity and then his profitability. One of the strategic aims that one proposes is reaches the positioning of the brand, which is fundamental for the growth to medium and long-term, nevertheless, our client distribution who are of shops and boutiques are vulnerable for the chains of stores of clothes that are located in the malls, which clients meet with major frequency, on the national level, for what our efforts have to be that to be increased to be kept as a solid company inside the market of fabrics in Quevedo.